Magnesium matters: unveiling hidden risks in kidney transplant patients through total and ionized magnesium profiling - Bocchi, Federica; Schietzel, Simeon; Huynh-Do, Uyen; Vogt, Bruno; Sidler, Daniel (Frontiers in Nephrology, 2024)
BackgroundIn kidney transplant (KT) patients, magnesium (Mg2+) deficiency is widespread. It is often encountered early after KT, may persist longer, and is frequently promoted by calcineurin inhibitors (CNIs) and tubular leakage. Studies demonstrated an association between post-KT hypomagnesemia and allograft dysfunction. The concentration of the active form, the ionized Mg2+ (iMg2+), is not measured clinically, and total Mg2+ (tMg2+) and iMg2+ correlations are conflicting. We assess the cross-sectional prevalence of hypomagnesemia in KT patients. The correlation of demographic and anthropometric parameters was also studied.MethodsA prospective, single-center analysis of KT patients was conducted at the University Hospital of Bern, Switzerland (March 2023–August 2023). Blood samples were collected at least twice for the majority of patients. tMg2+ has been quantified from a plasma sample at the Clinical Chemistry Department of the University Hospital of Bern. The PRIME® ES analyzer (Nova Biomedical, USA) provided results for iMg2+. The following co-variables were considered: age, comorbidities, kidney disease, KT history, estimated glomerular filtration rate (eGFR), and treatment (including Mg2+ supplementation and immunosuppression).ResultsA total of 208 measurements in 104 patients were performed [once in 9/104 patients (8.7%), twice in 86/104 (82.7%), and three times in 9/104 (8.7%)]. Compared to that in healthy volunteers (51 measurements in 51 participants), mean iMg2+ was significantly lower in KT patients KT: 0.46 mmol/L [interquartile range (IQR): 0.40–0.50], volunteers: 0.57 mmol/L (IQR 0.54–0.61), p < 0.01. Overall, iMg2+ and tMg2+ showed strong category agreement (r2 = 0.93, p < 0.01). In linear regression, low iMg2+ correlated with CNI exposure. For 110/208 measurements (52.9%), a reduced iMg2+ (cutoff: 0.42 mmol/L) was shown. In 58/208 (27.9%), both values were reduced, and 52/208 (25%) had isolated reduced iMg2+. In principal component analysis, patients with isolated low iMg2+ clustered with patients with low iMg2+ and tMg2+.ConclusioniMg2+ and tMg2+ were strongly correlated. A substantial proportion of patients show isolated low iMg2+. Currently, it is unclear if these patients suffer from Mg2+ deficiency.